Faktor Lingkungan Sosial Remaja PengkonsumsiMinuman Keras (MIRAS)(Studi Kasus pada Remaja Dukuh Wareg Desa NgarumKabupaten Sragen) - Prakoso, Ady; , Drs. Sutan Syahrir Zabda, M.Hum (2015)
Abstract This research purpose to: 1) description social enviromental has influence adolescent consumption liquor in Wareg Hamlet of Ngarum Village Sragen Regency, 2) description of solution to handled adolescent consumption liquor problem in Wareg Hamlet of Ngarum Village Sragen Regency. This research was taken by qualitative descriptive method. Subjek in this research was chief of neighbour foundation, citizen village and adolescent in Wareg Hamlet of Ngarum Village Sragen Regency. Research object was adolescent social enviromental has consumption liquor in Wareg Hamlet of Ngarum Village Sragen Regency. The data collecting technique in this research was interactive including interview, observation and documentation. This research use two kinds of triangulation, first triangulat the data source which was in the form of information from place, event and document loading note related to meant data. Second triangulation of data collecting technique coming from interview result, observation, and documentation. The data analyse technique in this research was using interactive model. Pursuant to result analyse concluded the followings: 1) Social enviromental factor has influencing liquor consumtion adolescent in Wareg Hamlet of Ngarum Village Sragen Regency, that was: a) dirty environment / poorness, b) The around society which was many out of job / have no the work. c) Workdload of old fellow and also family with its activity each so that child less affection. d) Broken home family. 2) Solution to overcome the liquor consumption adolescent problem in Wareg Hamlet of Ngarum Village Sragen Regency, that was founding Grounding Hall, creating balmy and peaceful house atmosphere, old fellow also instruct to child in chosening friend, and avoid the friend which like to consume the liquor, old fellow also give the workdload and entrust some of household responsibility to their children for the purpose so that the child can lessen the time outside activity time of ill defined at the same time train the child know the duty and obligation and also responsibility in household. Old fellow can create the balmy house atmosphere without only becoming old fellow but can become the friend to their children. Other solution also braid the communications better between old fellow with the child, and also cultivation assess the religion given early on so that child will not go into effect to look for the outdoors freshment and attention which can result fallen to the adolescent mischief in Wareg Hamlet of Ngarum Village Sragen Regency. Key word : social enviromental factor, adolescent, liquor